Monetary policy in low-inflation economies - Altig, David, 1956-; Nosal, Ed. (New York : Cambridge University Press, 2009)
This book looks at monetary and fiscal conditions for low inflation in terms of the advanced theories now used within central banks. It also brings together an excellent set of papers on the costs of inflation and the different perspectives afforded by leading alternative approaches to the same problem. They investigate the complications (or the lack thereof) of implementing monetary policy at low rates of trend inflation; threshold effects on the costs of inflation; and the interaction of inflation, financial markets and intermediation.
The welfare cost of inflation in the presence of inside money / Scott Freeman, Espen R. Henriksen, and Finn E. Kydland -- An open-economy model of endogenous price flexibility / Michael B.Devereux -- Efficient inflation targets for distorted dynamic economies / Costas Azariadis and Raphael W.K.Lam -- Inflation and welfare in models with trading frictions / Guillaume Rocheteau and Randall Wright -- Good versus bad deflation : lessons from the gold standard era / Michael D. Bordo, John Landon-Lane, and Angela Redish -- Monetary policy orientation in times of low inflation / Jürgen von Hagen and Boris Hofmann -- Observations on disinflation in transition economies / Paul Wachtel and Iikka Korhonen -- Inflation and financial market performance : what have we learned in the last ten years? / John Boyd and Bruce Champ.
Includes bibliographical references and index.
nmn 24/05/13
Loans
Keywords: Monetary policy; Inflation (Finance)